Knowledge, Attitude and Preventive Practices Regarding Hypertension among 40 Years and above Population Residing in Mahadevsthan, Kathmandu - Khatri, Elina; Mahabharata, SB; Yadav, RK; Devkota, N (Journal of Manmohan Memorial Institute of Health Sciences, 2019)
Background: Hypertension is a leading cause of cardiovascular diseases in both developed and developing countries. In recent time the epidemiological transition of countries from communicable diseases to non-communicable diseases had increased its importance. Hypertension had been ranked as a top five cause of mortality in Nepal. Assessment of knowledge, attitudes, and practices (KAP) is a crucial element ofhypertension control, but little information is available from developing countries where hypertension has lately been recognized as a major health problem.Objectives: To assess knowledge level, attitude and preventive practices regarding hypertension among 40 years and above population residing in Mahadevsthan, Kathmandu.Methodology: A cross sectional analytical study was conducted using Probability Proportionate Sampling (PPS) in 9 wards of Mahadevsthan, Kathmandu. Interview was done with closed ended Questionnaire for data collection among 165 respondents aged 40 years and above.Results:The study shows that the distribution of hypertension among respondents to be 22.4%. The mean age of respondents was 55 years with maximum of 97 years. The average knowledge score was 12.9 out of total 41 score. More than half of respondents i.e. 52.1% had a good knowledge on hypertension.